Students’ Responses to the Use of a Bilingual Pocket Dictionary - M. Hasby Hasbullah; Iin Baroroh Ma'arif; Ulfa Wulan Agustina; Nurul Afidah; Ahmad Kanzul Fikri; Hanifah Hanifah (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study explores students’ responses to the use of a bilingual (Arabic-English) pocket dictionary in learning activities at an Islamic boarding school in Jombang. The research employs a descriptive qualitative approach, involving students as participants. Data were collected through questionnaires, interviews, and classroom observations of the students of Al Munawaroh Islamic boarding school at Jombang. The findings indicate that the bilingual pocket dictionary significantly supports vocabulary acquisition, enhances learner autonomy, and increases motivation. However, some limitations include over-reliance on direct translation and limited contextual understanding. The study suggests integrating dictionary use with contextual learning strategies to optimize language acquisition.